Diseño del sistema de gestión en seguridad y salud en el trabajo en la empresa Constructora Edwin Hernández S.A.S (2021)
Constructora Edwin Hernández SAS does not have the Occupational Health and Safety Management System (SG-SST) established by Resolution 0312 of 2019, it was applied with a qualitative-interpretative approach where an initial evaluation was carried out with the 60 minimum standards. At the moment, no Occupational Health Safety actions are taken in any project, evidencing the greatest biological risks (Covid-19) and locative (falling objects). Taking into account the findings, it is possible to identify the need for the Design of the Occupational Health and Safety Management System applied to the Plan, Do, Verify and Act cycle in which it is necessary to carry out programs, formats, inspections, procedures, matrices, minutes, guides. Finally, the annual work plan that is included in the Management System gives the direction for the implementation from January 2022 to December 2022.